Management of Huntington’s disease: role of tetrabenazine - Marina de Tommaso; Claudia Serpino; Vittorio Sciruicchio (Dove Medical Press, 2011)
Marina de Tommaso, Claudia Serpino, Vittorio SciruicchioNeurological and Psychiatric Sciences Department, University of Bari Aldo Moro, Bari, ItalyAbstract: Huntington’s disease (HD) is an autosomal dominant neurodegenerative disorder characterized by progressive involuntary movements, neuropsychiatric disturbances, and cognitive impairment. The use of tetrabenazine (TBZ), a specific inhibitor of vesicular monoamine transporter, is approved for chorea in HD patients. We aimed to review the medical literature concerning the efficacy and tolerability of TBZ in the treatment of HD patients and to report our personal experience about TBZ use in a cohort of HD patients. We searched PubMed (1960 to July 2010) using the following keywords: “tetrabenazine” + “huntington’s disease + chorea”. We included randomized controlled trials, open-label trials, and retrospective studies. We excluded case reports and studies conducted on fewer than 20 patients. In addition, we retrospectively evaluated 2 years’ follow-up of TBZ treatment on motor and cognitive performances and functional abilities in 28 HD patients, compared with 10 patients treated by other neuroleptics (clotiapine). Only four papers fulfilled the requested criteria. In the first study, which included 84 randomized outpatients, TBZ showed a significant improvement of chorea compared with placebo. In the open-label study extension, TBZ confirmed its efficacy on chorea, with a frequent occurrence of withdrawals due to side effects. In a retrospective study of long-term efficacy, 63 patients under TBZ therapy for an average period of 34 months showed a stable effect on chorea, despite a slight reduction of effect over time. In a telephone survey conducted on a total of 118 patients affected by different movement disorders, TBZ showed the most favorable effect for the 28 included HD patients. Our HD patients showed a slight deterioration of motor performances over time that was nonsignificant compared with TBZ or clotiapine treatments. Despite the fact that the global effect of TBZ seems positive in HD, more attention on evaluating symptomatic treatments for cognitive and psychiatric deterioration as well as motor deterioration would alleviate this devastating disorder until a neuroprotective treatment becomes available.Keywords: Huntington’s disease, symptomatic treatment, tetrabenazine